2014
DOI: 10.1111/ecog.00963
|View full text |Cite
|
Sign up to set email alerts
|

Widespread native and alien plant species occupy different habitats

Abstract: Theories to explain the success of alien species often assume that they are inherently different from native species. Although there is an increasing body of evidence showing that alien plants tend to dominate in highly human‐modified environments, the underlying reasons why widespread natives might differ in their habitat distribution have rarely been addressed. We used species distribution models to quantify the dominant environmental axes shaping the habitat of 95 widespread native and alien herbaceous spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 59 publications
0
20
3
Order By: Relevance
“…This contrasts with other studies in which alien and native richness have been associated with similar drivers in the same direction (Fridley et al, 2007), or the same variables but in opposite directions (Polce et al, 2011;Greet et al, 2013;Tomasetto et al, 2013;Pouteau et al, 2015). At the broadest scale where we examined average differences in cover and richness among river reaches, no predictors were shared between the New Zealand alien and native plant communities.…”
Section: Discussioncontrasting
confidence: 89%
See 1 more Smart Citation
“…This contrasts with other studies in which alien and native richness have been associated with similar drivers in the same direction (Fridley et al, 2007), or the same variables but in opposite directions (Polce et al, 2011;Greet et al, 2013;Tomasetto et al, 2013;Pouteau et al, 2015). At the broadest scale where we examined average differences in cover and richness among river reaches, no predictors were shared between the New Zealand alien and native plant communities.…”
Section: Discussioncontrasting
confidence: 89%
“…Davis et al, richness and abundance of alien and native species. Yet other studies have found that while alien and native richness are often driven by the same variables, the nature of the underlying relationships can differ (Marini et al, 2009(Marini et al, , 2012Polce et al, 2011;Greet et al, 2013;Tomasetto et al, 2013;Pouteau et al, 2015). These divergent perspectives have been attributed to differences in the spatial scale at which relationships were examined (Fridley et al, 2007), yet, to date, few studies have attempted to assess the drivers of native and alien plant richness or abundance at different spatial scales (Brooks et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…The values of a particular trait may be normally distributed across all species in the native assemblage but exhibit significant inter-specific trait divergence (e.g., platykurtosis) among alien species even if no difference in trait means might be found between these two groups ( Figure 2c). An example might be where aliens comprise a wider spectrum of growth forms (e.g., annuals, biennials, short-and longlived perennials) than natives and result in a broader distribution in specific plant traits (Pouteau, Hulme, & Duncan, 2015). Despite mean trait values being similar, the inter-specific trait distributions reveal that aliens occupy under-exploited areas of niche space at the extremes of the trait distribution and this might explain the F I G U R E 2 Schematic to illustrate the importance of accounting for the shape of inter-specific trait distributions when comparing cooccurring native and alien species.…”
Section: Ne W In S I G Hts From Comparing Inter-s Pecifi C Tr Ait Dmentioning
confidence: 99%
“…Understanding how local species richness (α‐diversity) is distributed is a critical prerequisite for effective conservation strategies. Richness maps can provide the basis for selecting reserves (Cañadas et al., ; Moraes, Ríos‐Uzeda, Moreno, Huanca‐Huarachi, & Larrea‐Alcázar, ; Murray‐Smith et al., ; Raes, Roos, Slik, Van Loon, & ter Steege, ), prevention of biological invasions (Bellard et al., ; Gallardo, Zieritz, & Aldridge, ; Kelly, Leach, Cameron, Maggs, & Reid, ; Pouteau, Hulme, & Duncan, ), and mitigation of future impacts of climate change (Bellard et al., ; Brown, Parks, Bethell, Johnson, & Mulligan, ; Colombo & Joly, ; Fitzpatrick, Gove, Sanders, & Dunn, ; Midgley, Hannah, Millar, Thuiller, & Booth, ; Ogawa‐Onishi, Berry, & Tanaka, ; Siqueira & Peterson, ).…”
Section: Introductionmentioning
confidence: 99%